An empirical study to diagnose the outcomes of customers’ experiences in trendy coffee shops - Nadi̇ri̇, Halil; Gunay, G. Nazan (Journal of Business Economics and Management, 2013)
The purpose of this study is to analyse the influence of experiential marketing on young customers’ experiential values and respectively on their satisfaction and word of mouth and revisit intentions. An instrument was developed to measure how the strategic experiential module (Schmitt 1999) and service quality perceptions of customers influence their experiential values. Data were gathered through questionnaires conducted with 450 respondents to diagnose young customers’ experiences in Gloria Jean's Coffees shops in North Cyprus. The structural equation modelling through partial least square (PLS) method results were acceptable in terms of reliability and validity. The empirical results revealed that, some of the strategic experiential modules and service quality perceptions have positive influences on customer experiences (functional and emotional). Results also show that customers’ satisfaction can induce positive post purchase behaviour. The results, managerial implications, and suggestions for future research are discussed in detail.First published online: 12 Sep 2012